ANALYSIS OF THE ROLES OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Simunawir Sitoro; Mihani Mihani; Nuuridha Matiin (SEAN Institute, 2023)
Study this aim for knowing influence Among Environment work and Discipline work to employee performance at a national household appliance importer company. This research is study quantitative. Sample which taken as much 60 respondent. Tool measuring which used is questionnaire through google from. Data on study this use program SPSS 20. From the results of the analysis of the hypothesis that the work environment has no significant effect on performance employee, discipline work influential significant to performance employee.